(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Goal. To determine the effect of glycemic levels recorded during hospitalization for myocardial infarction (MI) on the early prognosis of patients without previously diagnosedдиа- бетаtype 2 diabetes 2 mellitus (DM - 2). Material and methods. A prospective examination of 296 patients was performed. Three groups were formed according to the level of glycemia at admission: I - 4.0 mmol/ l (7.4%); II-4.01–7.79 mmol/l (69.9%); III — 7.8 mmol/l (22.6%). The частота incidenceе- of нарушений carbohydrate metabolism disorders and развития MI complications ИМ in the hospital period was studied. Results. In 2/3 of patients with glycemia 7.8 mmol/l at поступле- нииadmission, later according to the standard glucose tolerance test (CTG) выявлены нарушения , carbohydrate metabolism disorders were detected: prediabetes (36.9%) and СД-2 type 2 diabetes (32.3%). У Patients III in group III were more likely to have three- fold поражение coronary artery disease (41.8%) and MI complications : congestive left ventricular failure-52.2% vs 27.3% in group I and 34.1% in II group II (p=0.017), cardiogenic shock - 26.9% vs 4.5% and 6.8% (p<0.001), нарушения conduction disturbances — 27.3% vs 9.1% and 11.7% (p=0.006), hospital mortality — 13.8% vs 4.5% and 4.4% (p=0.025). The risk of летального death in patients with glycaemia 7.8 mmol/ L was в 3.48 (95% CI: 1.41–8.60) times higher than при in patients with normal-glycaemiaниях(p=0.007). The glycemic index at admission was independently associated with the development of MI complications in the hospital period — OR=1.128; 95% CI: 1.005–1.266 (p=0.042), along with воз- age, depth of myocardial damage, and systolic blood pressure at admission. Conclusion. Early MI complications were more common among patients without a history of DM-2 who had a glycemic index at admission of 7.8 mmol/ l (22.6% of patients), чаще встречались ранние осложнения ИМ, and the risk of hospital mortality was 3 times higher than in other patients. The glycemic index at admission was an independent predictorofan unfavorable prognosis for MI in patients without previously diagnosed DM-2 and should be used in secondary- prevention measures вторичной.